Fresh Agricultural Products Cold Chain Logistics Development Status and Countermeasures Research - Jia, Jiyuan; Niu, Haohan; He, Yunqi (International Journal of Global Economics and Management, 2024)
With the improvement of the living standard of consumers in China, people are more and more concerned about the demand and quality of fresh agricultural products, and the market scale of cold chain logistics of fresh agricultural products is growing explosively. However, China's cold chain logistics still exists such as insufficient cold chain logistics infrastructure, low level of information technology, high cost, low degree of standardization of fresh agricultural products production and other problems, resulting in China's fresh agricultural products cold chain logistics is facing serious challenges. This paper analyzes the development status quo of cold chain logistics and puts forward some solutions to provide some references for subsequent research.